Hearing and Listening Difficulties in High Schools and Universities: The Results of an Exploratory Survey of a Large Number of Students and Teachers in the Friuli-Venezia Giulia and Umbria Regions, Italy - Valeria Gambacorta; Davide Stivalini; Niccolò Granieri; Raffaella Marchi; Alessia Fabbri; Pasquale Viola; Alessia Astorina; Ambra Fastelli; Giampietro Ricci; Eva Orzan (Audiology Research, 2025)
Background/Objectives: with the aim of describing how students and their teachers perceive and define their hearing and auditory experience in the classroom, we present the results of a questionnaire that examined the listening challenges faced by students and teachers at the University of Perugia and in four secondary schools in Friuli-Venezia Giulia, Italy. Methods: A survey was developed as part of the A.Ba.Co. project (Overcoming Communication Barriers). Closed or open-ended questions were used to analyze the responses of students and teachers regarding diagnosed or only perceived hearing difficulties in daily life and the quality of listening in school classes. Results: Hearing difficulties, either clinically diagnosed or only perceived, were reported by 8–9% of students. Between teachers, the reported hearing difficulties were 27.1% in high school and 12% at university (p < 0.001). The most frequent reason for less-than-optimal ease of listening in class differed between the two educational levels; 45.8% of high school students blamed it on the noise in the room compared to 18.2% of university students (p < 0.001). Inversely, 40.9% of university students connected listening difficulty with their place in class compared to 9.5% (101/1065) of high school students (p < 0.001). Conclusions: Although the minimum acoustic requirements for educational facilities have been established by the UNI 11532-2 standard, it is speculated that the majority of high school and university classrooms in Italy do not meet optimal listening conditions. Furthermore, the reasons for students’ poor listening quality appear to not be fully understood, neither by students nor by teachers. In addition to the need for greater attention to physical learning spaces (advocating the universal design principles), effective change will also need to involve a greater awareness of what the barriers to listening are and how much they influence both teaching and learning quality and effectiveness.